Green List: Standard to optimize the management effectiveness assessment of Protected Areas (Ecuador) - Mancheno Cáceres, María Karina; Bajaña Fabara, Diego Fernando (SATHIRI, 2025)
In this study, the management effectiveness assessment tool of Ecuador National Protected Areas System was optimized, based on adapting and including indicators and means of verification from the Green List Standard (IUCN). The main goals were to obtain results that respond to international schemes, reflect natural protected areas local context, support the information obtained in this kind of evaluation process and reduce subjectivity in the qualifications. The methodology consists of analyzing the tools taken as study basis, from which an optimized proposal tool was developed and that was validated by applying it on Cuyabeno Fauna Production Reserve as a pilot case. The main results showed that the Green List Standard has a high level of inclusion feasibility in the national tool, due to this, an optimized management effectiveness assessment questionnaire was developed and its validation results evidenced that the proposed questions achieved a high measurement capability, and the complete questionnaire contains indicators considered applicable and important for the evaluation. From this, functionality of the optimized proposal was demonstrated and the components provided by the Green List Standard contributed to make visible gaps that are not being considered in the management effectiveness assessment tool applied in Ecuador National Protected Areas System